PENGARUH PENGELOLAAN LABA TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN DENGAN MEKANISME CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING - Rochman Adi Bowo; Endang Kiswara (Diponegoro Journal of Accounting, 2014)
This  research  was  aimed  to  examine  empirically:  (1)  The  influence  of  earningsmanagement to CSR disclosure (2) The role of corporate governance mechanism as moderating variable  in  the  relationship  between  earnings  management  and  CSR  disclosure.  Corporategovernance mechanism was analyzed by proportion of independent commissioner, the number ofaudit committee meetings and board size. Earnings management was measured by discretionary accruals use Modified Jones Model and the extent of CSR was measured used corporate social reporting index (CSRI) based on Global Reporting Initiative (GRI) reporting standard items which were disclosed in companies annual report. This research used samples of company listed on Indonesia Stock Exchange 2012-2013. Data obtained from annual reports and sustainable reports of manufacturing companies listed on the IDX. There are 65 companies among 2012-2013 which fulfilling. The method of analysis of this research was multiple regression. This method was chosen because the independent variables are more than one and all the data of the variables are metric.This reseach found no significant statistical effect from various measurement of earnings management to CSR disclosure. The research also found there is no significant effect on proportion of independent commissioner, board size, and the number of audit committee meetings in relationship between earnings management and CSR disclosure. This research concluded that CSR is  driven  by  the  desire  to  meet  the  expectation  of  stakeholders  and  not  due  to  earnings management.  In  addition, the  formation  of the  board  of  commissioners  need  to  consider  the composition of ability and integrity of the members so that they can perform the function of monitoring, control and able to provide direction to management as well.